2020
DOI: 10.1016/j.clinbiomech.2020.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Adding a protective screw improves hinge's axial and torsional stability in High Tibial Osteotomy

Abstract: Backgrounds: Despite the use of a locking plate a 30% incidence of lateral hinge fracture after Open-Wedge High Tibial Ostetomy was described in the literature.A finite element model was used to analyze if the presence of a hinge-securing screw in the osteotomy area, using Patient Specific Cutting Guides with a locking plate, decreases the stresses within the lateral hinge during compression and torsion. Methods: A 3D model of a tibial sawbone was used to simulate an opening wedge of 10°. To apply loads on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…14 Previous studies have reported that protective wire or screw insertions may reduce the occurrence of hinge fractures and further displacement. 2,5,10 Based on these results, we suppose that a protective K-wire fixation may help prevent the LHF when a large correction (>11 mm of gap width) is planned.…”
Section: Discussionmentioning
confidence: 89%
“…14 Previous studies have reported that protective wire or screw insertions may reduce the occurrence of hinge fractures and further displacement. 2,5,10 Based on these results, we suppose that a protective K-wire fixation may help prevent the LHF when a large correction (>11 mm of gap width) is planned.…”
Section: Discussionmentioning
confidence: 89%
“…Accordingly, it can be deduced that the configuration (Figure 9) with a higher value of the reaction force (F) is more stable, and the one with a lower pressure (pmax) ensures reduced damage of the bone and, consequently, a higher stability of the implant. To obtain highly reliable numerical models, we set up the FEM models following a largely validated protocol [19,37,39]. Table 3 summarizes the main results obtained for each configuration analysed.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain highly reliable numerical models, we set up the FEM models following a largely validated protocol [19,37,39]. Table 3 summarizes the main results obtained for each configuration analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a FEM-based approach has been used and virtual simulations [24,46] have been performed using the commercial software Ansys Workbench (Ansys Inc., Canonsburg, PA, USA). To obtain highly reliable numerical models, the FEM models have been set up following a largely validated protocol [30,47,48]. Ten-node tetrahedral elements (SOLID187) were used to mesh the femur and the implant, and eight-node surface-to-surface (CONTA174 and TARGE170) contact elements [30] were used to mesh the bone/prosthesis interfaces (Figure 7).…”
Section: D Cad Modelling and Fem Modelmentioning
confidence: 99%